Pengaruh Rasio Likuiditas, Leverage dan Aktivitas Terhadap Profitabilitas Perusahaan Sektor Pertambangan di Bursa Efek Indonesia Periode 2013-2017 - Maritsa Aghniy; Hamid Bone; Dr. musviyanti musviyanti (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2021)
Maritsa Aghniy. The Effect of Liquidity Ratios, Leverage, and Activities on the Profitability of Mining Sector Company in Indonesia Stock Exchange 2013-2017 Period. This research was conducted under supervisor of Mr.Hamid Bone as supervisor I and Mrs. Musviyanti as supervisor II. The purpose of this study was to test the effect of liquidit, leverage and activity on profitability in a mining sector company. The population in this study all mining sector company in Indonesia Stock Exchange period 2013 to 2017 as many 39 companies, while the sample selection is done by using purposive sampling method were selected based on several criteria in order to obtain a sample 11 companies. The result of the analysis obtained value coefficient determination R square of 0,363 or 3,63%. This shows all the independent variables have an impact 36,3% on the dependent variable, while the remaining 6,37% is influenced by other variables. The result of research show that (1) there was a positive effect and partially not significant of liquidity (2) there was a negative effect and partially significant of leverage (3) there was a positive effect and partially significant of activity.